Correlation of serum adiponectin and leptin concentrations with anthropometric parameters in newborns - Palcevska-Kocevska, Snezana; Aluloska, Natasa; Krstevska, Marija; Shukarova-Angelovska, Elena; Kojik, Ljiljana; Zisovska, Elizabeta; Kocevski, Dragoslav; Kocova, Mirjana (Serbian Medical Society, 2012)
It has been shown that some adipocytokines and their mutual relationship can be indicators of fetal and neonatal growth. Physiological role of leptin and adiponectin in fetal and neonatal growth is not well established. Objectives. The aim of this study was to assess the correlation of the anthropometrics parameters and serum concentration of leptin and adiponectin levels in healthy newborns. Methods. A cohort of 110 neonates, born after uncomplicated singleton pregnancies at term, were classified as AGA (n=60), SGA (n=30) and LGA (n=20) according to the Lubchenco curves. Anthropometric parameters of the neonates: birth weight (BW), birth length (BL), body weight/body length ratio (BW/ BL), Body Mass Index (BMI) and Ponderal Index (PI) were recorded after birth. Results. Mean serum leptin and adiponectin levels in both sexes were not significantly different (male: 1.85±0.75; 29.51±22.89 and female: 2.06±0.99; 31.60±23.51 ng/mL). There was a significant difference between leptin levels in AGA and LGA newborns (1.93±0.84 vs. 3.12±1.50 ng/mL) (p<0.05), and in adiponectin levels between AGA and LGA compared to SGA newborns (32.8±23.29 and 43.40±31.24 vs. 12.67±2.43 ng/mL, respectively; p<0.05; p<0.05). Leptin and adiponectin levels were positively correlated with BW (r=0.63 and r=0.41), BL (r=0.63, r=0.42), BW/BL (r=0.61, r=0.41), BMI (r=0.54, r=0.35), and PI (r=0.47, r=0.29, (p<0.01). Conclusion. Significantly higher adiponectin levels were found in AGA neonates compared to SGA neonates. Leptin and adiponectine levels were positively correlated with birth weight. These findings suggest that these adipocytokines may be involved in fetal growth regulation.